Epigenetics of maternal-fetal interface immune microenvironment and placental related pregnancy complications - Ma, Xueqin; Chen, Xin; Mu, Xuefeng; Cao, Min; Zhang, Yan (Frontiers in Immunology, 2025)
Epigenetic regulation of placental development and pregnancy-related disease processes has recently been a hot research topic. Implantation and subsequent placental development depend on carefully orchestrated interactions between fetal and maternal tissues, involving a delicate balance of immune factors. Epigenetic regulation, which refers to altering gene expression and function without changing the DNA sequence, is an essential regulatory process in cell biology. Several epigenetic modifications are known, such as DNA methylation, histone modifications, non-coding RNA regulation, and RNA methylation. Recently, there has been increasing evidence that epigenetic modifications are critical for the immune microenvironment at the maternal-fetal interface. In this review, we highlight recent advances in the role of epigenetics in the immune microenvironment at the maternal-fetal interface and in epigenetic regulation and placenta-associated pregnancy complications.